ChemInform Abstract: Syntheses, Structures, and Reactions of Cyrhetrenylphosphines; Applications in Palladium Catalyzed Suzuki Cross‐Coupling Reactions. Issue 30 (29th July 2014) - Sierra, Diego; Bhuvanesh, Nattamai; Reibenspies, Joseph H.; Gladysz, John A.; Klahn, A. Hugo
Abstract The syntheses of four rhenium‐containing mono‐ and diphosphines are described.